ANDROGEN LEVELS IN PREECLAMPSIA - M. Valadan; N. Qadrdoost-Nakhchee F. Davari-Tanha (Acta Medica Iranica, 2006)
Preeclampsia is a major cause of morbidity and mortality during pregnancy. Several independent investigators have demonstrated the association of androgens with hypertension. The main purpose of this study was to determine whether maternal levels of sex hormones, especially testosterone, are higher in patients with preeclampsia than in matched normotensive control subjects. Serum levels of testosterone, free testosterone, dehydroepiandrosterone sulfate (DHEA-S) and estradiol were measured in 60 subjects in the 3rd trimester of pregnancy with documented preeclampsia (including 30 cases of mild and 30 cases of severe preeclampsia) and 60 healthy normotensive women with similar maternal and gestational ages and body mass index (BMI) and neonatal sex. All subjects were primigravid with singleton pregnancies. Cases of polycystic ovary (PCO), diabetes, chronic hypertension and chronic systemic diseases such as lupus and patients using steroid hormones and anti-hypertensive drugs were excluded. Levels of testosterone, DHEA-S and estradiol were not higher in primigravid women with preeclampsia than in normotensive women with similar gestational and maternal ages, BMI and neonatal sex. There were no significant differences in sex hormones measured between groups of mild and severe preeclampsia and normotensive women. There were also no significant differences in sex hormone levels according to neonatal sex. These findings are against the hypothesis of mediating or amplifying role of high androgen levels in pathophysiology of preeclampsia.